Neurons and Glia Cells in Marine Invertebrates: An Update - Ortega, Arturo; Olivares-Bañuelos, Tatiana N. (Frontiers in Neuroscience, 2020)
The nervous system of invertebrates and vertebrates (NS) is composed of two main types of cells: neurons and glia. In both types of organisms, nerve cells have similarities in biochemistry and functionality. The neurons are in charge of the synapse, and the glial cells are in charge of important functions of neuronal and homeostatic modulation. Knowing the mechanisms by which NS cells work is important in the biomedical area for the diagnosis and treatment of neurological disorders. For this reason, cellular and animal models to study the properties and characteristics of the NS are always sought. Marine invertebrates are strategic study models for the biological sciences. The sea slug Aplysia californica and the squid Loligo pealei are two examples of marine key organisms in the neurosciences field. The principal characteristic of marine invertebrates is that they have a simpler NS that consists of few and larger cells, which are well organized and have accessible structures. As well, the close phylogenetic relationship between Chordata and Echinodermata constitutes an additional advantage to use these organisms as a model for the functionality of neuronal cells and their cellular plasticity. Currently, there is great interest in analyzing the signaling processes between neurons and glial cells, both in vertebrates and in invertebrates. However, only few types of glial cells of invertebrates, mostly insects, have been studied, and it is important to consider marine organisms’ research. For this reason, the objective of the review is to present an update of the most relevant information that exists around the physiology of marine invertebrate neuronal and glial cells.